2018
DOI: 10.1111/ijd.14210
|View full text |Cite
|
Sign up to set email alerts
|

The clinical, biochemical, and ultrasonographic characteristics of patients with hidradenitis suppurativa in Northern Peninsular Malaysia: a multicenter study

Abstract: There was a male preponderance among HS patients in Northern Peninsular Malaysia with early age of onset and more severe disease. Only one-fifth had MetS, but they had significantly higher risks of obesity and low HDL. Ultrasonography examination was useful to detect subclinical lesions and providing a better understanding on disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 35 publications
1
53
1
Order By: Relevance
“…Genetic susceptibility is also likely a contributing factor to the association between HS and metabolic syndrome. Interestingly in our systematic review, the results of Loo et al . in Malaysian participants showed no significant association between HS and metabolic syndrome.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Genetic susceptibility is also likely a contributing factor to the association between HS and metabolic syndrome. Interestingly in our systematic review, the results of Loo et al . in Malaysian participants showed no significant association between HS and metabolic syndrome.…”
Section: Discussioncontrasting
confidence: 59%
“…Loo et al . performed a retrospective cross‐sectional case‐control study comparing 62 HS cases with 52 age and ethnic matched controls, from a Malaysian population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in the absence of therapeutic intervention, the disease progresses and the lack of early treatment may increase the number of complications that may develop . Ultrasound staging would allow for early clinical intervention to prevent, as much as possible, the potential progression of the disease …”
Section: Discussionmentioning
confidence: 99%
“…Different studies have suggested that US may help in HS management by enhancing the visualization and the extension of different cutaneous lesions, so to support an early diagnosis and a more precise assessment of disease severity …”
Section: Ultrasound In Hidradenitis Suppurativamentioning
confidence: 99%